Moral Lesson in Filosofi Kopi II Movie - Muhammad Bisyri; Agung Anugrah Ramadhani (HUMAN: South Asian Journal of Social Studies, 2022)
Abstract. The film philosophy i coffee II tells the story of two friends who are looking for an identity, a journey to make peace with past and success trough their coffee business. a story about how the struggle and hard work of two young men shows a meaning of the moral message contained in it and provides many lessons to be used as experiences in real life. The researcher used the Descriptive Qualitative research method, the subject of this study was the philosophy coffee II, while the unit of analysis was the cut scenes and dialogue contained in the philosophy coffee II The results of this study show that Roland Barthes’s theory of connotation and denotation, researchers can better understand the meaning or moral message contained in dialogue and scenes in the film philosophy coffe II. So that the delivery of information that opens up the thoughts and insights expected by the writer and audience of the film pylosophy coffe II provides a direct picture of friendship, affection, respect or mutual forgiveness. Keywords: Moral lesson, qualitative, semiotics